Adoption of Digital Payment Systems and its Effect on Financial Efficiency of Micro Enterprises in Rural Areas - Ary Yudianto; Jumai Latte (Jurnal Ilmiah Manajemen Kesatuan, 2026)
The increasing penetration of digital technologies has prompted rural microenterprises to adopt digital payment systems to enhance financial management and operational efficiency. This study investigates the adoption of digital payment systems such as QRIS, e-wallets, and mobile banking and their effects on the financial efficiency of micro enterprises in rural areas. The research aims to understand how the transition from traditional cash-based transactions to digital platforms influences cost reduction, transaction speed, and financial record accuracy among rural entrepreneurs. Using a mixed-method approach, data were collected through surveys and interviews with microenterprise owners who have adopted digital payment systems. Quantitative findings reveal a significant positive correlation between the frequency of digital payment use and improvements in financial management efficiency, particularly in reducing operational costs and enhancing transaction traceability. Qualitative analysis further highlights that digital payment adoption encourages better budgeting behavior and business transparency. However, barriers such as limited digital literacy and unstable internet access remain key challenges in rural implementation. The article discusses these findings in the context of Indonesia’s 2025 national agenda for digital economic transformation and provides policy implications for expanding inclusive digital finance in underserved regions.